Combination of Aloe vera and xenograft induction on decreasing of NF-kb of tooth extraction socket preservation in Cavia cobaya - Utari Kresnoadi; Retno Pudji Rahayu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: Tooth extraction can naturally cause inflammation triggering osteoclast proliferation and alveolar bone resorption. Preservation of the tooth extraction sockets is needed for patients in order to reduce alveolar bone resorption risks. Aloe vera is known to have anthraquinones components, namely Aloin, Aloe emedin, and barbaloin, considered as anti-inflammation. Therefore, to overcome the inflammation, the role of NF-kb is very significant to decrease nuclear factor kappa b (NF-kb). As a result, inflammation risks will be decreased. Purpose: The study was aimed to determine the induction effect of combination of Aloe vera and XCB into tooth extraction sockets to reduce inflammation by reducing NF-kb expression, osteoclasts and osteoblasts. Methods: Forty-eight Cavia cobaya were divided into eight groups, each group consisted of six animals. The mandibular incisors of those Cavia cobaya were extracted and induced with either PEG, XCB, Aloe vera, or the combination of Aloe vera + XCB. Those animals were sacrificed on day 7 and day 30 after the extraction. Then immunohistochemical and histopathology examinations were conducted to observe NF-kb expression, osteoblasts and osteoclasts. Results: It was known that in group induced with the combination of Aloe vera and xenograft concelous bovine, the growth of osteoblasts was high, while NF-kb expression and osteoclasts reduced. Conclusion: It can be concluded that the induction of the combination of Aloe vera and XCB into the tooth extraction sockets can reduce NF-kb expression and osteoclast, as a result, alveolar bone resorption risks decrease, and osteoblast increase.Latar belakang: Trauma mekanis akibat pencabutan gigi asli menyebabkan keradangan. Keradangan memicu proliferasi osteoklas sehingga menyebabkan resorpsi tulang alveolararis. Pada pembuatan gigi tiruan, resorpsi tulang alveolar yang terjadi, sangat tidak diinginkan, sebab resorpsi tulang alveolar mengurangi keberhasilan pembuatan gigitiruan. Diperlukan preservasi soket pencabutan gigi asli pada penderita untuk mencegah terjadinya resorpsi tulang alveolar. Aloe vera mempunyai komponen anthraquinon yaitu aloin, Aloe emodin, barbaloin yang merupakan anti inflamasi yang dapat secara cepat menyembuhkan luka, sehingga berpotensi untuk digunakan pada preservasi soket. Didalam mengatasi keradangan peran NF-kb sangat berarti, sebab penurunan NF-kb akan mengurangi terjadinya inflamasi. tujuan: Penelitian ini bertujuan untuk menguji apakah induksi kombinasi lidah buaya dan XCB ke soket pencabutan gigi dapat mengurangi peradangan dengan mengurangi ekspresi NF - kb , osteoklas dan osteoblast. Metode: Empat puluh delapan ekor Cavia cabaya yang terdiri dari 8 kelompok, tiap kelompok 6 ekor, kelompok pengisian PEG (kontrol), kelompok pengisian XCB, kelompok pengisian aloe vera dan kelompok pengisian kombinasi aloe vera dan XCB, kelompok ini terdiri dari kelompok 7 dan 30 hari, kemudian diperiksa dengan imunohistokimia ekspresi NF-kb dan pemeriksaan histologi untuk osteoblas dan osteoklas. Hasil: Kelompok yang diisi kombinasi Alo vera dan xenograft concelous bovine pada soket pencabutan gigi, menunjukan nilai tertinggi dalam pertumbuhan osteoblas dan penurunan pada ekspresi NF-kb dan osteoklas. Simpulan: Induksi kombinasi Aloe vera dan xenograft concelous bovine pada preservasi soket pencabutan gigi dapat menurunkan ekspresi NF-kB dan osteoklas, menurunkan resiko resorpsi tulang alveolar dan meningkatkan osteoblas.